System Dynamic Analysis of the Fleet Availability and Reliability Influence on the Lead Time of the Delivery Order Process - Windyaningrum, Theresia Liris; Indrawati, Chatarina Dian; Long, Zalizah Awang; Prasetyo, Vinsensius Widdy Tri; Waloyo, Lorensius Anang Setiyo; Murdapa, Petrus Setya (Indonesian Journal of Information Systems, 2023)
The inventory replenishment process in the warehouse becomes difficult if there is uncertainty. It can cause warehouse performance not to be as expected. The warehouse is an important part of the supply chain subsystem, which smooths the flow of goods from upstream to downstream throughout the system. This paper uses system dynamics modeling to analyze the replenishment of raw materials where there is randomness in availability and reliability and their effects on the delivery lead time of the fleet. The model obtained is much simpler but more robust when compared to the analytical-mathematical model or the discrete-events simulation. Tests on the model show that the model can behave as it should logically. Several experiments were conducted to see how fleet availability's reliability can affect the delay in receiving or delivery lead time. One interesting thing revealed is that reliability does not have to be 100%, but there is a certain minimum threshold for the system to perform well. This is different from availability, which must be 100%.